2015
DOI: 10.1051/0004-6361/201425038
|View full text |Cite
|
Sign up to set email alerts
|

Passive galaxies as tracers of cluster environments atz~ 2

Abstract: Even 10 billion years ago, the cores of the first galaxy clusters are often found to host a characteristic population of massive galaxies with already suppressed star formation. Here we search for distant cluster candidates at z ∼ 2 using massive passive galaxies as tracers. With a sample of ∼40 spectroscopically confirmed passive galaxies at 1.3 < z < 2.1, we tuned photometric redshifts of several thousand passive sources in the 2 sq. deg COSMOS field. This allowed us to map their density in redshift slices, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 78 publications
1
31
0
Order By: Relevance
“…Studies of the morphologies of cluster galaxies have shown that significant numbers of cluster galaxies at z>1.5 have disturbed or irregular morphologies (Mei et al 2015;Santos et al 2015), and mergers have also been taken to explain the larger sizes of high-redshift cluster galaxies compared to otherwise similar galaxies in the field (e.g. Delaye et al 2014;Strazzullo et al 2015). A recent study by Alberts et al (2016) focussed on galaxy clusters in the range 1<z<2, and concluded that environmental interactions and an increased galaxy merger rate were triggering the heightened AGN fraction in the cores of some 11 massive clusters.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the morphologies of cluster galaxies have shown that significant numbers of cluster galaxies at z>1.5 have disturbed or irregular morphologies (Mei et al 2015;Santos et al 2015), and mergers have also been taken to explain the larger sizes of high-redshift cluster galaxies compared to otherwise similar galaxies in the field (e.g. Delaye et al 2014;Strazzullo et al 2015). A recent study by Alberts et al (2016) focussed on galaxy clusters in the range 1<z<2, and concluded that environmental interactions and an increased galaxy merger rate were triggering the heightened AGN fraction in the cores of some 11 massive clusters.…”
Section: Discussionmentioning
confidence: 99%
“…A significant fraction of cluster SFGs and ETGs have been observed to have disturbed morphologies in z > 1.5 clusters (Mei et al 2015;Santos et al 2015). Minor and/or dry mergers may additionally explain the larger size of quiescent galaxies in clusters at high redshift relative to the field Bassett et al 2013;Delaye et al 2014;Strazzullo et al 2015).…”
Section: Sf and The Cluster Environmentmentioning
confidence: 99%
“…This decreases to´-2.0 10 4 considering only Ksfaint radio sources, and to 10 −5 and 10 −7 for sources with > z 1.5 phot and < < z 2 3 phot , respectively. A more objective approach is to use S 5 peak statistics 12 to search for overdensities in the full COSMOS field, following the method from Strazzullo et al (2015), which allows for a derivation of the dispersion and thus for an evaluation of their significance. Figure 3 shows the resulting S 5 maps and distribution of S 5 readings over the full COSMOS areas for the various selections described in Table 2.…”
Section: Radio Selection Of the Z=25 W16 Clustermentioning
confidence: 99%
“…More typical  z 2 systems have been discovered looking for concentrations of massive galaxies (e.g., Gobat et al 2011Gobat et al , 2013Yuan et al 2014;Strazzullo et al 2015;Wang et al 2016), and X-ray emission searched for at their known positions, a posteriori.…”
Section: Introductionmentioning
confidence: 99%